Conspicuous consumption for social parity - Chinmayi Srikanth; Shubhasis Dey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The extant literature on status-signalling primarily adopts Veblen's theory of class to caste and racial identities. This study aims to adopt a more suitable theoretical lens that is more relevant not only for class identities, but also for other identities such as caste and race. By viewing conspicuous consumption within the Stigma-Identity-Threat framework, this study analyses how socially disadvantaged groups in India respond to stigma through their consumption behaviour. Using two rounds of the India Human Development Survey data (2004-05 and 2011-12), we study whether disadvantaged social groups embrace or distance themselves from their stigmatized identity. We find that SC (Scheduled Castes), ST (Scheduled Tribes), and OBC (Other Backward Classes) households among caste groups, and Muslims among religious groups, tend to move away from their devalued identities. While OBCs achieve this through productive expenditures, SCs, STs, and Muslims use unproductive means
Keywords: A12; D12; J15; O12; 330; Stigma-Identity-Threat; conspicuous consumption; caste; class; status-signalling